The relationship between balance performance, lumbar extension strength, trunk extension endurance, and pain in participants with chronic low back pain, and those without. (March 2018) - Behennah, Jessica; Conway, Rebecca; Fisher, James; Osborne, Neil; Steele, James
Abstract: Background: Chronic low back pain is associated with lumbar extensor deconditioning. This may contribute to decreased neuromuscular control and balance. However, balance is also influenced by the hip musculature. Thus, the purpose of this study was to examine balance in both asymptomatic participants and those with chronic low back pain, and to examine the relationships among balance, lumbar extension strength, trunk extension endurance, and pain. Methods: Forty three asymptomatic participants and 21 participants with non-specific chronic low back pain underwent balance testing using the Star Excursion Balance Test, lumbar extension strength, trunk extension endurance, and pain using a visual analogue scale. Findings: Significant correlations were found between lumbar extension strength and Star Excursion Balance Test scores in the chronic low back pain group ( r  = 0.439–0.615) and in the asymptomatic group ( r  = 0.309–0.411). Correlations in the chronic low back pain group were consistently found in posterior directions. Lumbar extension strength explained ~19.3% to ~37.8% of the variance in Star Excursion Balance Test scores for the chronic low back pain group and ~9.5% to ~16.9% for the asymptomatic group. Interpretation: These results suggest that the lumbar extensors may be an important factor in determining the motor control dysfunctions, such as limited balance, that arise in chronic low back pain. As such, specific strengthening of this musculature may be an approach to aid in reversing these dysfunctions. Highlights: Chronic low back pain is associated with lumbar extensor deconditioning. This may affect balance ability in this population. We investigated the relationship between these two variables. Lumbar extension strength may contribute to balance ability. Lumbar extensor strengthening should be examined to improve balance.